2022
DOI: 10.20448/jeelr.v9i2.4030
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Attitudes towards using the Nearpod Application in Distance Learning

Abstract: Creating a stimulating learning environment is a challenge in distance learning settings. This study aimed to investigate university students' attitudes towards using Nearpod in distance learning. For purposes of the study, the researchers developed a questionnaire of 20 items for which the validity and reliability were verified. The study sample consisted of 190 students. The students were taught different courses remotely in the second semester of the academic year 2020-2021 via Nearpod and Zoom. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Nearpod integration in learning does not only affect the interactive learning process but also increases students' positive attitudes. [13] conducted a study of 190 students to see whether Nearpod integration could improve students' attitudes towards learning. Musa found that students showed a positive attitude when learning was integrated with Nearpod.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearpod integration in learning does not only affect the interactive learning process but also increases students' positive attitudes. [13] conducted a study of 190 students to see whether Nearpod integration could improve students' attitudes towards learning. Musa found that students showed a positive attitude when learning was integrated with Nearpod.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results showed that teacher support was the most important variable (x ̅ =3.69)." [13] "Nearpod helped connect faculty and students during a time when remote learning was required. Grades on examinations stayed consistent or were higher, evenwith the abrupt changes made due to the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides students with various engaging features, motivating them to learn (Feri & Zulherman 2021). Because of its inventiveness and pedagogical value, learning with this application is more interactive (Musa & Al Momani 2022). The application can be used as an assessment instrument in learning, providing timely and effective feedback (Nurhamidah 2021;Shehata et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…using the help of interactive movies, gaming activities, polls, quizzes, and collaboration boards, teachers may promote active learning using Nearpod, an affordable and user-friendly interactive learning tool (Sarginson & McPherson, 2021). Nearpod app can be used in faceto-face learning or through virtual classroom synchronization (Musa & Al Momani, 2022). This research is supported by several relevant previous studies, namely: (1) The Nearpod application learning media is feasible to use and can be proven to improve the learning outcomes of fifth grade students of SDN 2 Blimbing Kidul, Kaliwungu, Kudus (Pramesti et al, 2023).…”
Section: Introductionmentioning
confidence: 99%